A hybrid PSO-SA scheme for improving accuracy of fuzzy time series forecasting models - Phong, Pham Dinh; Duc Du, Nguyen; Hoang Hiep, Pham; Thanh, Tran Xuan (Journal of Computer Science and Cybernetics, 2022)
Forecasting methods based on fuzzy time series have been examined intensively during last years. Three main factors which affect the accuracy of those forecasting methods are length of intervals, the way of establishing fuzzy logical relationship groups, and defuzzification techniques. Many researches focus on optimizing length of intervals in order to improve forecasting accuracies by utilizing various optimization techniques. In the line of that research trend, in this paper, a hybrid particle swarm optimization combined with simulated annealing (PSO-SA) algorithm is proposed to optimize length of intervals to improve forecasting accuracies. The experimental results in comparison with the existing forecasting models show that the proposed forecasting model is an effective forecasting model.